Effect of genistein on IGF‐1 and IGFBP‐1 in young and aged female rat ovary - Chi, Xiao‐xing; Zhang, Tao; Chu, Xiao‐li (Journal of animal physiology and animal nutrition, 2019)
The objective of this study was to assess the effects of genistein (GEN) on expression of insulin‐like growth factor 1 (IGF‐1) and insulin‐like growth factor binding protein 1 (IGFBP‐1) in young and aged rat ovary. Forty young female Sprague Dawley (SD) rats (200 ± 20 g) and forty aged female SD rats (490 ± 20 g) were selected and according to weight, they were divided into the following five groups with eight animals in each: negative control group (NC), low‐dose group (L), middle‐dose group (M), high‐dose group (H) and positive control group (PC). GEN group received GEN of 15, 30, 60 mg/kg respectively. It lasted 30 days. Concentrations of serum hormones, IGF‐1 and IGFBP‐1 were determined by enzyme‐linked immunosorbent assay (ELISA). Gene and protein expressions of IGF‐1 and IGFBP‐1 were determined by real‐time PCR and Western blot respectively. Compared with NC, GEN significantly increased oestradiol‐17β(E2) level in aged rat, reduced luteinizing hormone (LH) level in young and aged rat. Serum levels of IGFBP‐1 in young rats were significantly higher in GEN groups (p < 0.05). mRNA and protein expression levels of IGF‐1 and IGFBP‐1 were positively correlated with GEN dose. GEN could significantly reduce the ratio of IGF‐1/IGFBP‐1 of aged rats. Multivariate Cox regression analysis result showed IGF‐1 and IGFBP‐1 levels significantly correlated with GEN dose. We speculate that there is an association between the addition of GEN and expression of IGF‐1 and IGFBP‐1, and the relationship between them is different in young and aged rat.